Curriculum Planning based on Economic Knowledge in Some Developed Countries - Khorasgani, Amir Toghyani; Jahanbaksh Rahmani, (IJRDO- Journal of Educational Research, 2019)
Trade deficits, stock market woes, inflation, and the energy crisis are examples of economic problems in almost every under development countries during the past three decades. However, it is unlikely that most citizens understand what created these kinds of problems or how leaders have tried to solve them. This lack of knowledge is a consequence of insufficient emphasis on economics in the general education of citizens. This paper uses an integrated approach to examine the impact of a knowledge based economy on curriculum. It discusses a generic profile of an effective knowledge worker and how countries are responding to the challenge. This study shows how to plan and develop a new curriculum model based on economy. To meet the desired educational outcomes, it complements curriculum changes with a pedagogic approach that transforms the role of teachers to facilitators of learning.